2022
DOI: 10.7759/cureus.29141
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence of Small Bowel Obstruction in Adults After Operative Management of Adhesive Small Bowel Obstruction: A Systematic Review

Abstract: The objective of this article is to review the existing literature on postoperative recurrence of adhesive small bowel obstruction (ASBO). We performed a systematic review following Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, searching PubMed, Cochrane Library, and Google Scholar, to identify randomized controlled trials (RCTs) and observational studies investigating recurrence after operative management of ASBO. Our search yielded one RCT, one prospective study, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…As shown in our study, the risk of developing NI-SBO was higher in patients with a history of SBR. This is consistent with previous studies that have examined adhesive SBOs and found that the number of previous laparotomies, bowel injuries, operative times, perioperative bleeding, and diffuse adhesions (or matted adhesions) were all significantly associated with recurrent hospitalizations for SBO [ 22 - 24 ]. The results of this study suggest that while the probability of developing NI-SBO after a first resection is low, prevention of CD recurrence after a first resection is critical, and clinicians should likely start/optimize therapy to avoid the need for repeat resection.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…As shown in our study, the risk of developing NI-SBO was higher in patients with a history of SBR. This is consistent with previous studies that have examined adhesive SBOs and found that the number of previous laparotomies, bowel injuries, operative times, perioperative bleeding, and diffuse adhesions (or matted adhesions) were all significantly associated with recurrent hospitalizations for SBO [ 22 - 24 ]. The results of this study suggest that while the probability of developing NI-SBO after a first resection is low, prevention of CD recurrence after a first resection is critical, and clinicians should likely start/optimize therapy to avoid the need for repeat resection.…”
Section: Discussionsupporting
confidence: 91%
“…On the other hand, although laparoscopy has been shown to be associated with decreased adhesion formation, it has not been associated with a lower incidence of SBO in colorectal surgery [ 16 ]. Two other meta-analyses found no benefit with regard to reoperation for adhesion in patients undergoing laparoscopic procedures compared to those undergoing open procedures [ 24 , 26 ]. Furthermore, no significant benefits were found between the two approaches in the “conventional vs. laparoscopic-assisted surgery in colorectal cancer” trial, which compared the incidence of adhesion-related complications, particularly SBO, after laparoscopic and open colorectal surgery [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Conservative management is still the treatment of choice for managing adhesive SBO with high success rates. In non-responding cases, surgical dense adhesiolysis might by followed with recurrent severe adhesions [ 6 ]. This fact supports the consideration of conservative treatment as the first line of therapy for mildly symptomatic ACS.…”
Section: Discussionmentioning
confidence: 99%
“…The thickened fibrotic membrane encapsulating the bowel with the dense adhesions prevent the vascular pedicle from twisting [ 8 ]. Therefore, the necessity for bowel resection in such a case is less common compared with when a band is the cause of intestinal obstruction [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Surgical intervention poses the concern of creating new adhesions, while pursuing a non-operative treatment leaves the adhesions in place. 12 However, two studies found that delaying surgical intervention was associated with increased mortality, morbidity, and length of stay (LOS). 7,11 Several other studies have investigated the differences in patient care and outcomes when a patient is admitted to MS vs SS.…”
Section: Introductionmentioning
confidence: 99%